Okara flour: its physicochemical, microscopical and functional properties - Santos, Daiane Costa dos; Oliveira Filho, Josemar Goncalves de [UNESP]; Silva, Jhessika de Santana; Sousa, Milena Figueiredo de; Vilela, Marcio da Silva; Pereira da Silva, Marco Antonio; Lemes, Ailton Cesar; Egea, Mariana Buranelo (Emerald Group Publishing Ltd, 2019)
Purpose Okara, which is the residue of hydrosoluble extract from soybean obtained after soymilk and tofu production, has high nutritional value and can be used for ingredient in specific food products. This study aims to evaluate the production and properties (physicochemical, microscopical and functional ones) of okara flour (OF) obtained from okara as a by-product of soymilk and tofu production. Design/methodology/approach Wet okara resulted from the soymilk process underwent convective drying up to reach mass stability (60 degrees C for 12 h). OF properties were analyzed by official methods by AOAC, i.e. mineral composition was evaluated by atomic absorption equipment; color; water absorption index (WAI); milk absorption index (MAI); oil absorption capacity (OAC); and foam capacity (FC) required mixtures with water, milk and oil, separation and gravimetry, respectively; and microstructure was determined by a scanning electron microscope. Findings Results showed the potential OF has as a source of protein (24.74 g/100 g) and dietary fiber (58.27 g/100 g). Regarding its color after the drying process, OF was markedly yellow (b* parameter 20.16). Its WAI was 3.62 g/g, MAI was 4.33 g/g, OAC was 3.68 g/g and FC was 1.32 per cent. The microscopic analysis of OF showed that both loose and agglomerated particles had irregular structures and indefinite forms. Originality/value Production of flour from wet okara can be an alternative use of this by-product. This study showed important characteristics of OF and its possible application to the food industry. Thus, OF was shown as a potential ingredient with high nutritional value.
Keywords: Fiber; By-product; Protein; Conservation method; Value-added ingredient